2021
DOI: 10.1155/2021/5173190
|View full text |Cite
|
Sign up to set email alerts
|

Association of NFE2L2 Gene Polymorphisms with Risk and Clinical Characteristics of Acute Type A Aortic Dissection in Han Chinese Population

Abstract: The present study is aimed at investigating the association of NFE2L2 gene polymorphisms with risk and clinical characteristics of acute type A aortic dissection (AAAD) in a Han Chinese population. Six SNPs (rs1806649, rs13001694, rs2364723, rs35652124, rs6721961, and rs2706110) in NFE2L2 were genotyped using SNaPshot Multiplex Kit in 94 adult patients diagnosed with AAAD at our hospital, and 208 healthy Han Chinese subjects from the 1000 Genomes Project were served as the control group. The CC genotype of rs2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Nuclear factor E2-related factor 2 (NRF2) is encoded by the NFE2L2 gene, and the NRF2/ARE signaling pathway is considered a potential therapeutic strategy for antioxidative stress-mediated diseases, such as diabetes, fibrosis, and cancer ( Thiruvengadam et al, 2021 ). NFE2L2 polymorphism is associated with acute type A aortic coarctation risk and severity in a Chinese Han population ( Zhang et al, 2021 ). RAD21, RELA, and TAL1 are reportedly associated with tumors ( Wu et al, 2019 ; Cao et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor E2-related factor 2 (NRF2) is encoded by the NFE2L2 gene, and the NRF2/ARE signaling pathway is considered a potential therapeutic strategy for antioxidative stress-mediated diseases, such as diabetes, fibrosis, and cancer ( Thiruvengadam et al, 2021 ). NFE2L2 polymorphism is associated with acute type A aortic coarctation risk and severity in a Chinese Han population ( Zhang et al, 2021 ). RAD21, RELA, and TAL1 are reportedly associated with tumors ( Wu et al, 2019 ; Cao et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, if confirmed in larger cohorts, the evidence of a deleterious effect of the minor genotype of rs2364723 on the oxidative stress of patients with poor glycemic control would have a significant relevance, especially in clinical contexts with a high prevalence of patients with poor glycemic control. The CC genotype of rs2364723 has been previously associated with major cardiovascular events and reduced heart rate variability [ 9 , 13 ]. Similar to our results, the minor allele of rs2364723 has been associated with the risk of complications in patients with type 2 diabetes of both Chinese and European ancestry [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic variation at NFE2L2 has been associated with vascular function (forearm blood flow), autonomic function (heart rate variability), major vascular events and type 2 diabetes complications in cohorts and case control sets of adults [ 9 , 10 , 11 , 12 , 13 ]. Especially, the minor allele of rs2364723, which is in complete linkage disequilibrium with the promoter SNP rs35652124, known to impede the NFE2L2 transcriptional activity, has been consistently associated with unfavorable outcomes [ 9 , 10 , 11 , 12 , 14 , 15 ]. We have previously observed that the concentration of serum derivatives of reactive oxygen metabolites (d-ROMs) is increased compared to healthy peers in a cohort of 412 children/adolescents with T1D [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…NFE2L2 controls cellular response to oxidative insults, thus preventing damage to components sensitive to redox changes such as proteins, lipids and DNA. NFE2L2 is a putative regulator of the cardiac stress-response [85], and it has been found that NFE2L2 gene polymorphisms are associated with the risk and severity of acute type A aortic dissection [86]. MARCHF6 is a ubiquitin ligase embedded in the membranes of the ER, which participates in ER-associated degradation, including autoubiquitination [87].…”
Section: Protein Processing In the Endoplasmic Reticulum (Er) Pathwaymentioning
confidence: 99%